Which equation represents g(x)?
g(x) ^3 square root of x+ 1 g(x) = ^3 square root of x - 1
g(x) = ^-3 square root of x + 1
g(x) = ^-3 square root of x - 1

Please help!! I’ll live you forever!!!

Which equation represents gx gx 3 square root of x 1 gx 3 square root of x 1 gx 3 square root of x 1 gx 3 square root of x 1 Please help Ill live you forever class=

Respuesta :

Answer:

F(x) = - cuberoot (x-1)

Last answer

Step-by-step explanation:

Graphing calculator

Hope this helps! You'll live me forever??? you have some powers 0_0 (I think you meant love* )

Answer:d

Step-by-step explanation: edge 2021 ;)

ACCESS MORE